Recent update on application of propolis as an adjuvant natural medication in management of gum diseases and drug delivery approaches. (January 2022) - Parolia, Abhishek; Bapat, Ranjeet Ajit; Chaubal, Tanay; Yang, Ho Jan; Panda, Sourav; Mohan, Mandakini; Sahebkar, Amirhossein; Kesharwani, Prashant
Graphical abstract: Highlights: Propolis has historically been widely used to alleviate several diseases. Propolis is shown to be promising in the treatment of gum diseases. Effect of propolis and its application as an adjuvant natural medication is discussed. Abstract: Propolis has historically been widely used to alleviate several diseases and has gained attention of researchers from various disciplines. It is a resinous material produced by honeybees with various biological properties. Based on the current evidence, it is shown to be promising in the treatment of gum diseases such as gingivitis and periodontitis as a safe and effective antibacterial agent for periodontopathic bacteria. It has been used in different formulations such as toothpaste, mouthwash, or local drug delivery with specific type of propolis in appropriate concentration for efficient action. Propolis has high antibacterial property, it acts by damaging the cell membrane, causing leaking of cell contents and ultimately cell death. It also impedes cell mobility by inhibition of adenosine triphosphate (ATP). The main advantage of propolis is that it is a non-toxic biomaterial with bacteriostatic and bactericidal properties with sustained release effect. It also displays anti-inflammatory, antioxidant, and antifungal action. It is highly effective in treatment of root canal infections and gum diseases. However, it should be used with caution in patients who are allergic to bee products as it may cause allergic reactions. The antibacterial action of propolis is influenced by its type, place of origin, season, plant type, method of extraction and concentration of use. Hence, the solution to this problem is, a development of standardized methodology by industry to confirm its safer and effective use in the clinical setting. Propolis has been used with various drug delivery approaches for treatment of dental caries, pulpal infection, periodontal infection and local drug medicaments. This review provides an extensive overview and update on the effect of propolis and its application as an adjuvant natural medication in the management of gum infections especially like periodontitis and recommends studies with robust methodologies to confirm the antibacterial effects of propolis in future.